Simulated transfer dynamics of blood on to cardboard and comparison to simple fluids for blood substitute development and assessment. Issue 1 (2nd January 2017) - Stotesbury, Theresa; Taylor, Michael C.; Jermy, Mark C.
ABSTRACT: Synthetic blood substitutes (SBSs) have value in bloodstain pattern analysis (BPA) for research, training and case reconstruction experimentation. This work addresses the performance testing of SBSs using reproducible laboratory methods to simulate the formation of common bloodstain pattern types. This study has extended a previously reported protocol that was restricted to drip stain characteristics, to include the SBS performance assessment in transfer patterns with characteristics of the originating object. The process of formation of transfer bloodstains was investigated using a cylindrical roller with a constant applied pressure. Samples of porcine blood, human blood, and Millipore water were used to create transfer patterns on cardboard over three depletions. The quality of the transfer was established by measuring pattern resolution, by counting the number of distinguishable objects across the print. A statistical template that defines the expected transfer pattern appearance of both blood and water is presented. The template was then applied to several candidate SBSs using a points scoring system. Samples of a dilute adhesive, honey and a solution of 30% w/v glycerol and 10% w/v starch gave the highest scores for transfer simulation. The roller test method can be used to understand the minimum size of features that can be reliably interpreted in a transfer pattern.